Analisis Perbandingan Kualitas Laba Sebelum dan Sesudah Implementasi Psak 71 pada Perbankan yang Terdaftar Di Bursa Efek Indonesia - Siti Khusfatun Khasanah; Agrianti Komalasari (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This research is motivated by the implementation of a new financial accounting standard, namely PSAK 71, the adoption of IFRS 9 revision 2017 which has just begun to be effectively implemented in Indonesia starting in early 2020. This study aims to analyze the comparison of earnings quality between before and after the implementation of PSAK 71 in banks that listed on the Indonesia Stock Exchange. By using quantitative methods. Data were collected by purposive sampling method. The population in this study are banks listed on the Indonesia Stock Exchange in 2019 and 2020 as many as 47 banks. The sample used in this study were 41 banks that met the criteria. Data analysis in this study was conducted using the paired-samples t-test. Based on the results of the paired-samples t-test in this study, it shows that there is no significant difference in earnings quality between before and after the implementation of PSAK 71